Farmer support regime and political economy of agricultural reform: transformation of Turkish agricultural policy in the post-2000 era - Koçak, Ayşe. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2012., 2012)
This thesis analyzes the changing dynamics in post-2000 agricultural policy making in Turkey in terms of populist electoral tradition in relation to the international and domestic policy dynamics. The focus of the study is early 2000s when the reform moves gained a renewed pace as a result of the international pressures’ winning leverage over the incumbent governments of the era following the 2001 economic crisis. The thesis takes a snapshot of the trajectories in agricultural policy making and reform efforts in the sector and reveals the changing nature of governmental policy attitude towards agriculture in the early 2000s While analyzing the evolution of the agricultural support regime and policy making in Turkey of the Justice and Development Party (AKP) government era, starting from 2002 until 2011, the international and domestic roots of the reform move and the erratic governmental policy and discourse changes towards the agricultural sector are traced. The main hypothesis of the thesis is that the early years of the AKP rule do not exemplify a deviation from populist policy tradition in Turkish agriculture but was more of an “obligated” policy transfer to save the day. The initial reason for AKP’s seemingly leading away from populist-corporatist electoral tradition in agriculture was mainly because of the AKP’s weak capacity in handling electoral promises and populist legacy while trying to adhere to its promises to international pressure groups and lack of an innovative and comprehensive policy alternative rivalling the reform designs of the World Bank and IMF. However, once it gained more political power with the help of a more stable economic and political environment and ensured some space to wriggle out of IMF constraints, the initial determination for reform on part of the AKP government did not last long and agricultural policy making started to move back again on the populist-corporatist electoral track with the introduction of agricultural policies deviating from the IMF and the WTO principles and original aims of the WB backed ARIP. In the end, the populist tradition in agriculture survived a new wave of reform pressure striking a happy medium with the old and new policies for the sake of the new giving way to a hybrid and disorienting agricultural regime with the future prospects of hatching into new and more radical policy reforms.
Keywords: Agricultural policy -- Turkey.; Agriculture and state -- Turkey.; Agriculture -- Economic aspects -- Turkey.; Produce trade -- Turkey.